Do recruitment patterns of young men who have sex with men (YMSM) recruited through respondent-driven sampling (RDS) violate assumptions?. Issue 12 (1st August 2014) - Phillips, Gregory; Kuhns, Lisa M; Garofalo, Rob; Mustanski, Brian
Abstract : Background: To generate unbiased estimates for data collected using respondent-driven sampling (RDS), a number of assumptions need to be met: individuals recruit randomly from their social network and people can accurately report their eligible network size. However, research has shown that these assumptions are often violated. Methods: This study used baseline data from Crew 450, a longitudinal study of young men who have sex with men in Chicago who were recruited via a modified form of RDS and its network substudy, in which a subset of 175 participants reported details on the composition and characteristics of their social network at either 1 or 2 years postbaseline. Results: Nearly two-thirds of participants reported giving coupons to at least one alter (64%), and 56.3% believed their alter(s) used the coupons. Frequency of communication, closeness and type of relationship played a major role in determining coupon distribution. Participants whose alters used coupons were significantly less likely to describe the strength of their relationship as 'not at all close' (OR=0.08; 95% CI 0.02 to 0.36) compared with 'very close' and to communicate weekly (OR=0.20; 95% CI 0.08 to 0.49) or 1–6 times in the past 6 months (OR=0.18; 95% CI 0.06 to 0.59). Conclusions: Contrary to RDS assumptions, we found that relationship characteristics played a significant role when individuals decided to whom they would give coupons.